LIVING AROUND THE MINES (AN ANTHROPOLOGICAL STUDY ON SOCIAL CHANGE AND ADAPTATION STRATEGIES OF THE LELILEF WAIBULEN COMMUNITY TOWARD THE PRESENCE OF PT IWIP MINING INDUSTRY) - M. Rizal Rizky Ramli; Syahrir Ibnu; Jusan Hi Jusuf (Social Studies and Humanities Journal (SOSHUM), 2025)
This study aims to analyze the social change and adaptation strategies of the Lelilef Waibulen community, Central Halmahera, in response to the presence of PT Indonesia Weda Bay Industrial Park (IWIP). Employing a qualitative ethnographic approach, data were collected through in-depth interviews, participant observation, and field documentation. The findings reveal that the community’s economic transformation from an agrarian to an industrial and informal service economy has triggered changes in social structure, cultural values, and local power relations. These transformations can be understood through Pierre Bourdieu’s theory of social practice and Anthony Giddens’ structuration theory, as elaborated by Ibnu (2024), which emphasize the dialectical relationship between structure and agency. Furthermore, Ibnu’s (2023) study on local governance and regulation shows that industrialization often produces social inequality and weakens community sovereignty. The research concludes that the Lelilef Waibulen community is not merely a victim of change but an adaptive social actor that negotiates its socio-economic space amid industrial pressures. These findings contribute to the anthropology of development and socio-ecological studies in extractive industry regions.